Stimuli-Directing Self-Organized 3D Liquid-Crystalline Nanostructures: From Materials Design to Photonic Applications - Wang, Ling; Li, Quan (Advanced functional materials, 2016)
3D photonic nanostructures with desirable functionalities in the visible light region and beyond have been recently given vast and increasing attentions because of the ability to control or confine electromagnetic waves in all three dimensions. Although substantial progress has been made in fabricating 3D nanostructures by means of lithography and nanotechnology, various bottlenecks still need to be overcome, and developing soft 3D stimuli‐directed nanostructures with tailored properties remains a challenging but exciting work. In this context, soft nanotechnology—i.e., exploiting self‐organized soft materials in nanotechnology—is emerging as a vibrant and burgeoning field of research in the bottom‐up nanofabrication of intelligent stimuli‐driven 3D photonic materials and devices. Liquid‐crystalline materials undoubtedly represent such a marvelous dynamic system that combines the liquid‐like fluidity and crystal‐like ordering from molecular to macroscopic material levels. Importantly, being “soft” makes the materials responsive to various stimuli such as temperature, light, mechanical force, and electric and magnetic fields as well as chemical and electrochemical reactions, resulting in a fascinating tunability of dynamic photonic bandgaps in the 3D nanostructure that provides numerous opportunities in all‐optical integrated circuits and next‐generation communication systems. Here, the development of 3D photonic nanostructures is reviewed, culminating with perspectives for the future scope and challenges of these emerging soft 3D photonic nanostructures towards device applications. Soft nanotechnology—i.e., exploiting self‐organized soft materials in nanotechnology—is emerging as an attractive paradigm in the bottom‐up nanofabrication of intelligent stimuli‐driven 3D photonic materials and devices. Liquid‐crystalline materials undoubtedly represent such an elegant dynamic system that combines the liquid‐like fluidity and crystal‐like ordering from molecular to macroscopic levels. This review provides a glimpse of the advancements in design, fabrication and applications of stimuli‐directing self‐organized 3D liquid‐crystalline photonic nanostructures.